STRATEGI PEMASARAN UMKM MELALUI PENGGUNAAN E-COMMERCE DALAM MENINGKATKAN PENJUALAN DI ERA DIGITALISASI - Oni Tiana (2023)
The purpose of writing this final project is to find out the marketing strategy of MSMEs in Sawangan District, Depok City by selling their products using an e-commerce system, to find out the role of e-commerce for MSMEs in Sawangan District, Depok City and to see the advantages and disadvantages of using e-commerce. commerce for MSMEs and consumers. The data obtained in this Final Project Report was by distributing questionnaires to MSMEs in Sawangan District, Depok City with 7 sub-districts each with one respondent, distributing questionnaires to consumers in Sawangan District, Depok City and interviewing MSME administrators in Sawangan District, Depok City. From the results the author has found that e-commerce plays an important role for MSMEs in Sawangan sub-district, especially in the culinary business sector because by using e-commerce their income increases and can make it easier for MSMEs in digital marketing. Consumers also argue that they prefer to shop online.